Optimization of the Electrical Properties of PVDF Nanofibers with the Addition of P3HT and PCBM Processed by Electrospinning - Pedro Leonardo Silva; Bruno Henrique de Santana Gois; André Antunes da Silva; Vagner dos Santos; Vitor Hugo Uzeloto Fernandes Mingroni; Giovana Aibara Miti Paschoal; Patrik Diones de Santana Gois; Valdemiro Pereira de Carvalho Júnior; Clarissa de Almeida Olivati; Roger Clive Hiorns; Deuber Lincon da Silva Agostini (Materials Research)
In this study, electrospun nanofibers of poly(vinylidene fluoride) (PVDF) were produced with the addition of [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) and poly(3-hexylthiophene) (P3HT), for application as a nanostructured active layer of bulk heterojunction polymer with fullerene and polythiophene derivatives in third-generation photovoltaic devices. The electrospinning technique was used to favor the formation of the β phase, exhibiting ferroelectric properties, improving the electrical performance of the device. The morphological, structural and electrical characteristics of the nanofibers were investigated using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and DC electrical measurements. The synergism between nanofiber processing and the addition of P3HT and PCBM improved electrical conductivity by up to three orders of magnitude, furthermore, the nanofibers incorporating P3HT exhibited responses to solar stimuli.